Ni2+ and Cd2+ Biosorption Capacity and Redox-Mediated Toxicity Reduction in Bacterial Strains from Highly Contaminated Soils of Uzbekistan - Aziza Usmonkulova; Eligio Malusa; Gulchekhra Kadirova; Ilkhom Khalilov; Loredana Canfora; Liliya Abdulmyanova (Microorganisms, 2025)
In this study, Ni2+ and Cd2+ resistant Pseudomonas aeruginosa 18, Enterobacter ludwigii 11Uz, and Enterobacter cloacae Uz_5 strains were isolated from soils contaminated with heavy metals in the Samarkand and Kashkadarya regions (Uzbekistan), and tested to remove Ni2+ and Cd2+ ions from the environment via biosorption. The biosorption capacity of these strains was observed under in vitro conditions. The biosorption process was highly dependent on the growing conditions, with the highest biosorption rate observed after 300 min of incubation at pH 7.0, and 40 °C. The presence of functional groups such as S=O, NH2, and COOH in the biosorbing microorganisms was confirmed by IR spectroscopy. The adsorption capacity decreased when the initial metal concentration was increased and was enhanced with higher microbial biomass. Enterobacter ludwigii 11Uz strain was found to alter the toxic oxidation state of Ni2+ and Cd2+ cations, while Pseudomonas aeruginosa 18 and Enterobacter cloacae Uz_5 strains reduced the toxicity of Ni2+ cations only by changing their oxidation state. It was confirmed in our studies that the three selected bacterial strains actively participated in the detoxification of Cd2+ through the synthesis of cysteine amino acid.